2014
DOI: 10.15560/10.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Bivalves of the São Sebastião Channel, north coast of the São Paulo state, Brazil

Abstract: The north coast of the São Paulo State, Brazil, presents great bivalve diversity, but knowledge about these organisms, especially species living subtidally, remains scarce. Based on collections made between 2010 and 2012, the present work provides a species list of bivalves inhabiting the intertidal and subtidal zones of the São Sebastião Channel. Altogether, 388 living specimens were collected, belonging to 52 species of 34 genera, grouped in 18 families. Tellinidae, Veneridae, Semelidae, Ungulinidae, Mactrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…In contrast, Grande Island is located in an estuarine complex with the best conserved mangrove areas in northeastern Brazil (Carlos et al 2010, Barroso et al 2013. Although not addressing the malacofauna of estuarine regions, other taxonomic studies (e.g., Longo et al 2014, Tallarico et al 2014, Duarte et al 2014 report somewhat similar compositions and abundances for the taxonomic groups found in the present investigation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In contrast, Grande Island is located in an estuarine complex with the best conserved mangrove areas in northeastern Brazil (Carlos et al 2010, Barroso et al 2013. Although not addressing the malacofauna of estuarine regions, other taxonomic studies (e.g., Longo et al 2014, Tallarico et al 2014, Duarte et al 2014 report somewhat similar compositions and abundances for the taxonomic groups found in the present investigation.…”
Section: Discussionsupporting
confidence: 62%
“…in the São Sebastião Channel on the northern coast of the state of São Paulo (southeastern Brazil). Tallarico et al (2014) provide a list of 52 bivalve species inhabiting the intertidal and subtidal zones of the São Sebastião Channel. Duarte et al (2014) found 65 mollusk species in three shallow-water reef habitats along the coast of the state of Paraíba.…”
Section: Discussionmentioning
confidence: 99%
“…The organisms were collected from the intertidal zone, where they live buried under sandy and muddy sediments (Tallarico et al 2014). Specimens were removed from the sediment with a shovel, manually sorted using a sieve and immersed in sea water, transported and processed at the Centre of Marine Biology, University of São Paulo (CEBIMar-USP).…”
Section: Methodsmentioning
confidence: 99%
“…Most species are now restricted to relatively limited geographic ranges and have specialized niches being, therefore, considered a group of rare species (Coan & Valentich‐Scott, ; Harper, Dreyer, & Steiner, ; Harper, Hide, & Morton, ; Morton, ). Species from the families Cuspidariidae, Pandoridae, Periplomatidae and Thraciidae have been recorded from the northern coast of São Paulo state, in southeastern Brazil (Amaral & Nallin, ; Migotto, Tiago, & Magalhães, ; Salvador, Domaneschi, Amaral, Morgado, & Henriques, ; Soares‐Gomes & Pires‐Vanin, ; Tallarico et al, ).…”
Section: Introductionmentioning
confidence: 99%